PENGENALAN OLAHRAGA TRADISIONAL DI ERA DIGITAL DI SDN PADOMASAN 03: - Atho'illah, Muhammad Hifni; Ahmad Sulaiman (Jurnal Bakti Masyarakat Indonesia, 2025)
This dedication will highlight the importance of preserving traditional sports in the current digital era. Traditional sports have many benefits both for students' physical and motor skills. This research uses intensive methods and lectures carried out in socialization. A total of 54 class V students at SD Negeri Padomasan 03 became partners in this service. There are four stages in this service, namely planning and preparing activities and disseminating material, implementing service activities, monitoring and evaluation. Percentage formulas for descriptive statistics are used in data analysis techniques. Research findings show that students' understanding has changed from ignorance to knowledge. With the help of technology and the internet, students can find out the meaning of traditional sports, their advantages, the importance of maintaining traditional sports, and various forms of traditional sports carried out throughout Indonesia.